2017
DOI: 10.1111/jpn.12730
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of sweet potato (Ipomoea batatas (L.) Lam) in broiler diets

Abstract: SummaryCereal grains such as maize and wheat are used extensively in feed formulations for poultry as the primary source of carbohydrates. High cost of these grains in many developing countries necessitates the evaluation of other ingredients that are grown locally. Sweet potato is one such crop. The study was conducted as a proof of concept experiment to test the hypothesis that in the presence and absence of enzyme, sweet potato roots when included in diets of broiler chickens may affect the total metabolisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…In the current study, the counts (log CFU/g) of total enterobacteria and E.coli from the ceca of birds fed with the different dietary treatments were not significantly influenced by the different SP varieties and enzyme supplementation. This observation is similar to our earlier experiment [19] using sweetpotato flour in which the counts of the total enterobacteria and E. coli were not influenced by the inclusion of sweetpotato flour or enzyme supplementation.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, the counts (log CFU/g) of total enterobacteria and E.coli from the ceca of birds fed with the different dietary treatments were not significantly influenced by the different SP varieties and enzyme supplementation. This observation is similar to our earlier experiment [19] using sweetpotato flour in which the counts of the total enterobacteria and E. coli were not influenced by the inclusion of sweetpotato flour or enzyme supplementation.…”
Section: Discussionsupporting
confidence: 91%
“…Fibres are plant food components not transformed by digestion. The fibres tested on poultry induced variable modulations of body weight or feed intake without modulating the FCR [ 46 , 50 , 51 ], which was explained by the absence of modification of the structure of the villi of the small intestine [ 46 , 50 , 51 , 52 ]. In some studies, the fibres were able to induce an increase in the abundance of lactic-acid-producing bacteria and a decrease in the abundance of zoonotic and/or pathogenic bacteria such as Salmonella and Escherichia coli [ 30 , 46 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, higher mortality was recorded for broilers when sweet potato meal inclusion levels were greater than 25% (Maphosa, Gunduza, Kusina, & Mutungamiri, ). Similarly, a recent study also reported that diets containing 250 g/kg sweet potato flour led to poor growth of broilers (Pandi, Glatz, Forder, Komolong, & Chousalkar, ). Therefore, processed sweet potato or its waste has potential for use in poultry feed, but their inclusion levels need to be considered.…”
Section: Introductionmentioning
confidence: 86%